Temporary polymer bonding for the manufacturing of thin wafers: An innovative low temperature process. (1st March 2021) - Montméat, P.; Bally, L.; Dechamp, J.; Enot, T.; Fournel, F.
Abstract: The study deals with the handling of thin wafers in 3D integration. It concerns the fabrication of 300 mm wafers in industrial tools. Usually, the manufacturing is based on a temporary bonding process performed at 200 °C using a thermoplastic adhesive. In that condition bonding, thinning and dismounting are satisfactory. Moreover, the adhesive flattening during bonding results in an excellent thickness uniformity of the bonded pairs, with a small total thickness variation (TTV) value suitable for 3D integration. If the temperature is 150 °C or lower, the adhesive thickness uniformity is not acceptable anymore. An innovative temporary bonding process at low temperature has thus been developed. It consists in a carrier fabrication with highly uniform adhesive thickness. The standard coated adhesive is flattened with a first reversible temporary bonding at 210 °C. After a first dismounting, this carrier is then bonded to the target device wafer with a low bonding temperature, from 110 °C to 150 °C. Due to the pre-flattening, 80 μm thick silicon films with an excellent TTV value can thus be obtained even with a low bonding temperature required by the device wafer. Moreover, after the device wafer thinning, the final dismounting can be performed without any antisticking layer.